A deep learning-based approach to model anomalous diffusion of membrane proteins: the case of the nicotinic acetylcholine receptor - Buena Maizon, Héctor (2022)
Fil: Buena Maizon, Héctor. Pontificia Universidad Católica Argentina. Instituto de Investigaciones Biomédicas. Laboratorio de Neurobiología Molecular; Argentina